2013
DOI: 10.1097/bot.0b013e318271f8f0
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Injury to the Anterior Tibial Artery in the Posterolateral Approach to the Tibia Plateau

Abstract: Background: Posterolateral tibial plateau shear fractures often require buttress plating, which can be performed through a posterolateral approach. The purpose of this study was to provide accurate data about the inferior limit of dissection.Methods: Forty unpaired cadaver adult lower limbs were used. The anterior tibial artery was identified because it coursed through the interosseous membrane. The perpendicular distance from the lateral joint line and fibula head to this landmark was measured.Results: The an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 18 publications
1
50
0
3
Order By: Relevance
“…In most patients, the posterior region fracture was posterior-lateral shearing or depression. As the posterior-lateral region is complex because of the peroneal nerve [21] and anterior tibial artery [22], we applied an oblique plate and left proximal holes empty just for a posterior blocking. The reduction of the posterior-lateral fracture was from an anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…In most patients, the posterior region fracture was posterior-lateral shearing or depression. As the posterior-lateral region is complex because of the peroneal nerve [21] and anterior tibial artery [22], we applied an oblique plate and left proximal holes empty just for a posterior blocking. The reduction of the posterior-lateral fracture was from an anterior approach.…”
Section: Discussionmentioning
confidence: 99%
“…Merely, in the third zone, the most posterior part, the posteromedial approach was used [14][15][16]. The posterolateral approach presents the possibility of iatrogenic neurovascular damage such as the anterior tibialis artery [17], and venous bleeding during soft tissue exfoliation for xation of distal screws often causes problems with hematoma and wound recovery [18]. Also, later, it is di cult to remove the plate due to the formation of scar tissue and adhesion on the plate when the plate needs to be removed later.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we used the tibial tuberosity as the reference anatomical landmark to make our measurements in order to determine the location of the IOF and ATA in the vertical and horizontal planes in the proximal portion of the leg with palpation. In contrast, the studies by Ebraheim et al [13] and Heidari et al [14] used the tibial plateau and head of the fibula as reference anatomical landmarks to determine the location of the IOF in the vertical plane during surgical interventions. Ebraheim et al [13] reported the average length of the tibia in their study was 30.1 ± 2.2 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using cadaver dissections of the leg have been performed to identify the relationship of the ATA to the tibia [13] and to measure the length and width of the IOF for surgical interventions [14]. However, no studies have been performed to identify the surface projection of the IOF and ATA in the proximal leg with palpation.…”
Section: Introductionmentioning
confidence: 99%